2021
DOI: 10.3390/cancers13194893
|View full text |Cite
|
Sign up to set email alerts
|

Anti-PD-1/Anti-PD-L1 Drugs and Radiation Therapy: Combinations and Optimization Strategies

Abstract: Immune checkpoint inhibitors have been associated with long-term complete responses leading to improved overall survival in several cancer types. However, these novel immunotherapies are only effective in a small proportion of patients, and therapeutic resistance represents a major limitation in clinical practice. As with chemotherapy, there is substantial evidence that radiation therapy promotes anti-tumor immune responses that can enhance systemic responses to immune checkpoint inhibitors. In this review, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 106 publications
0
12
0
Order By: Relevance
“…Recently, the abscopal effect induced by radiotherapy has drawn increased attention. Studies have shown that radiotherapy could exert immunomodulatory effects that may result in antitumor responses, especially when combined with checkpoint inhibitors (19)(20)(21). Li and colleagues found that the expression of PD-1 was increased in patients receiving radiation, indicating the potential combination of PD-1 inhibitors and radiation (22).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the abscopal effect induced by radiotherapy has drawn increased attention. Studies have shown that radiotherapy could exert immunomodulatory effects that may result in antitumor responses, especially when combined with checkpoint inhibitors (19)(20)(21). Li and colleagues found that the expression of PD-1 was increased in patients receiving radiation, indicating the potential combination of PD-1 inhibitors and radiation (22).…”
Section: Discussionmentioning
confidence: 99%
“…Targeted drugs against cytotoxic T-lymphocyte associated protein 4 (CTLA4) and programmed cell death receptor 1 (PDCD1, also known as PD-1)/programmed cell death receptor ligand 1 (PDCD1LG1, also known as PD-L1) play an anti-tumor effect by relieving tumor cells’ inhibition of T cell function ( O'Donnell et al, 2017 ). In recent years, immune checkpoint inhibitors (ICI), as the most common immunotherapy, have brought hope for treating malignant tumors ( Boustani et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“… 26 A similar technique known as Lattice radiation also administers ablative variable doses of RT to large tumors and helps with preserving surrounding organs at risk. 27 SBRT‐PATHY (stereotactic body radiation therapy‐based partial tumor irradiation targeting hypoxic segment of bulky tumors) is another technique that was developed by Tubin et al to harness hypoxia in bulky tumors where stereotactic body radiation therapy is administered to partial tumor mass irradiation technique. 19 , 27 FLASH‐RT (FLASH Radiotherapy_ which utilizes novel radiotherapy technology with single ultra‐high dose‐rate (≥40 Gy/s) radiotherapy and microbeam radiation therapy are lesser known techniques that are being investigated for abscopal response as well).…”
Section: Introductionmentioning
confidence: 99%
“… 27 SBRT‐PATHY (stereotactic body radiation therapy‐based partial tumor irradiation targeting hypoxic segment of bulky tumors) is another technique that was developed by Tubin et al to harness hypoxia in bulky tumors where stereotactic body radiation therapy is administered to partial tumor mass irradiation technique. 19 , 27 FLASH‐RT (FLASH Radiotherapy_ which utilizes novel radiotherapy technology with single ultra‐high dose‐rate (≥40 Gy/s) radiotherapy and microbeam radiation therapy are lesser known techniques that are being investigated for abscopal response as well). 19 , 28 Out of these techniques, the SBRT‐PATHY has shined to hold relevant promise in inducing abscopal response as it takes into account radiation‐induced bystander effect, manipulating tumor hypoxia, protecting the peritumoral environment and partial irradiation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation